Pediatric sport injuries: When to refer or X-ray - Lyon, R. M.; Street, C. C. (Pediatric Clinics of North America, 1998)
When any athlete presents for evaluation of an injury, the history and physical examination is of paramount importance in establishing a differential diagnosis. A radiograph is often used to confirm a diagnosis or to reassess an injury following treatment failure. There are certain drawbacks involved with getting a radiograph including cost, inconvenience, radiation exposure, and misinterpretation. Therefore, the radiographic evaluation of the injured athlete should be used only as clinically necessary. The benefits of getting a radiograph, to allow assessment of the severity of the injury, and thereby allow a more appropriate and aggressive treatment and rehabilitation program. The skills of history taking and physical examination presented in this article should make it easier to decide when the child athlete needs a more comprehensive and aggressive evaluation including radiographic studies. The content of this article: Spine Obere Extremitäten Shoulder Elbow and Forearm Wrist and Hand Lower extremity Hip and Pelvis Knee Ankle and Foot Summary References